Kecerdasan emosional sebagai pemoderasi pada faktor-faktor yang mempengaruhi kecurangan akuntansi - Alfiati Silfi; Devi Savitri; Astrid Faradisty (Pelantar Press, 2022)
The objective of the study is to investigate the influence between Asymetry information, Compensation suitable and Organization culture ethic toward Accounting fraud with Emotional Intelligence as Moderated variable. The sample in this study is from 89 respondents at OPD of Indragiri Hulu goverment in Riau province. Data were analyzed with SPSS by regression analysis and Moderated Regression Analaylis to examine the influence of Asymetry information, Compensation suitable and Organization culture ethic toward Accounting fraud. The result shows that hypotheses 1, 2 and 3 are eaccepted. But the hypotheses 4, 5 and 6 are not accepted.